Strategies for Improving Healthcare Workers’ Compliance with Infection Control Measures in Intensive Care Units: A Systematic Review and Meta-Analysis - Abdullah Alshehari; Abdullah Saeed (Intensive Care Research)
Abstract Background This review and meta-analysis assessed strategies for improving Healthcare Workers HCWs’ adherence to Infection Control Measures ICMs while working in an ICU since the setting provides a potentially high risk for HAIs. Methods Of these, 103 studies were identified to meet the inclusion criteria and, therefore, were included, which reported intervention studies conducted in ICUs with the purpose of promoting HCWs’ adherence to ICMs. Results The results indicate that the most effective strategies are multimodal-education linked to feedback, simulations, and other applications that achieve a 23.6% improvement in compliance, with consistent effectiveness across settings. Educational interventions alone achieved an average improvement of 16.13% and showed large variability, depending on the context. Conclusion Multimodal strategies surpass educational strategies in improving adherence to ICMs. Health facilities should adopt comprehensive, multimodal strategies to improve patient safety and reduce HAIs, and future efforts should refine these approaches for broader applications.